Suicide attempts by adolescents assisted in an emergency department: a cross-sectional study - Vanessa Dias Fogaça; Danton Mateus de Souza; Lucía Silva; Danila Maria Batista Guedes; Flavia Domingues; Isadora Trinquinato; Lisabelle Mariano Rossato (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify and characterize the care provided to adolescents admitted to an emergency department due to a suicide attempt. Methods: an observational, cross-sectional, descriptive study with a retrospective approach, carried out with medical records of adolescents aged 10 to 19 admitted for suicide attempts, between January 2015 and July 2020, in an emergency department. Data were subjected to descriptive and inferential analysis. Results: eighty-eight service occurrences were identified, mainly to females, exposed to multiple risk factors. Exogenous intoxication was the main method used, occurring at home and on weekdays. There were systemic repercussions, requiring multiple interventions and hospitalizations. Only 26% of cases were notified. Conclusions: adolescents treated for suicide attempts were exposed to multiple risk factors, with intoxication as the main means used. There is concern about the underreporting of cases and the logic of clinical care and medicalization.